"I think it's something that we should lean in to": The use of OpenNotes in Canadian psychiatric care contexts by clinicians. (December 2022) - Kassam, Iman; Shin, Hwayeon Danielle; Durocher, Keri; Lo, Brian; Shen, Nelson; Mehta, Rohan; Sockalingam, Sanjeev; Wiljer, David; Gratzer, David; Sequeira, Lydia; Strudwick, Gillian
Background: OpenNotes is the concept of patients having access to their health records and clinical notes in a digital form. In psychiatric settings, clinicians often feel uncomfortable with this concept, and require support during implementation. Objective: This study utilizes an implementation science lens to explore clinicians' perceptions about using OpenNotes in Canadian psychiatric care contexts. The findings are intended to inform the co-design of implementation strategies to support the implementation of OpenNotes in Canadian contexts. Method: This qualitative descriptive study employed semi-structured interviews which were completed among health professionals of varying disciplines working in direct care psychiatric roles. Data analysis consisted of a qualitative directed content analysis using themes outlined from an international Delphi study of mental health clinicians and experts. Ethical approval was obtained from the Centre for Addiction and Mental Health and the University of Toronto. Results: In total, 23 clinicians from psychiatric settings participated in the interviews. Many of the themes outlined within the Delphi study were voiced. Benefits included enhancements to patient recall, and empowerment, improvements to care quality, strengthened relational effects and effects on professional autonomy and efficiencies. Despite the anticipated benefits of OpenNotes, identified challenges pertained to clarity surrounding exemption policies, training on patient facing notes, managing disagreements, and educating patients on reading clinical notes. Conclusion: Many benefits and challenges were identified for adopting OpenNotes in Canadian psychiatric settings. Future work should focus on applying implementation frameworks to develop interventions that address the identified challenges.